2017
DOI: 10.1111/jam.13573
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the infection risk of enteropathogens from consumption of raw vegetables washed with contaminated water in Kathmandu Valley, Nepal

Abstract: It is needed to protect vegetable washing water sources and establish advanced water treatment methods to achieve the required level of public health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…were detected at the highest concentration in the river water sample, which is widely used for several purposes, such as irrigation and washing vegetables prior to sale in the Kathmandu Valley. Activities that use polluted river water may pose diarrheal risks from waterborne pathogens, such as enteropathogenic E. coli , Giardia , and Cryptosporidium , via the consumption of raw contaminated vegetables ( 42 ). Waterborne outbreaks of gastroenteritis have also been linked to the contamination of Arcobacter spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…were detected at the highest concentration in the river water sample, which is widely used for several purposes, such as irrigation and washing vegetables prior to sale in the Kathmandu Valley. Activities that use polluted river water may pose diarrheal risks from waterborne pathogens, such as enteropathogenic E. coli , Giardia , and Cryptosporidium , via the consumption of raw contaminated vegetables ( 42 ). Waterborne outbreaks of gastroenteritis have also been linked to the contamination of Arcobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…In the Kathmandu Valley, 34% of individuals use alternative water sources, such as ground, jar, tanker, rain, spring, stone spout, and river water as domestic supplies ( 41 ). Various microbiological studies on water samples have been conducted ( 17 , 20 , 21 , 26 , 29 , 35 , 38 , 42 , 45 ), resulting in the detection of fecal indicator bacteria, pathogenic bacteria, protozoa, and viruses in ground, surface, irrigation, and even jar water (which is perceived as potable). In our previous study conducted in the Kathmandu Valley, a next-generation sequencing (NGS) analysis demonstrated that Acinetobacter , Arcobacter , and Clostridium were highly abundant in ground and river water samples, and that Arcobacter was the second most dominant pathogenic bacterium and present in all 16 samples tested, with a maximum abundance ratio of 17.43% ( 17 ).…”
mentioning
confidence: 99%
“…The high contamination rates recorded in the open-market samples indicate poor hygiene in these locations, which is suitable for the propagation and transmission of the parasites [72]. High risk of diarrhea among raw vegetable consumers in the Kathmandu valley of Nepal, mostly due to the use of river water by farmers for washing vegetables, suggests a need to avoid the use of river water for washing vegetables [73]. There are also many reports that highlight the contamination of surface water with parasitic infective stages in Brazil [74], Iran [75], Poland [76] and Spain [77].…”
Section: Risk Factors Involved In the Contamination Of Vegetables Andmentioning
confidence: 99%
“…Industrial pollution load, poor sewage and wastewater treatment facilities, inadequate water pollution control laws, and rapid urbanization have all contributed to the increased degradation of the river water environment in developing countries [1,2]. The Bagmati River, which flows from the northern boundary southwards across the urban areas of the Kathmandu Valley in Nepal, is suffering from chemical, biological, and solid waste pollution [1,[3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%